2013
DOI: 10.1088/1674-1056/22/7/077308
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar resistive switching based on bis(8-hydroxyquinoline) cadmium complex: Mechanism and non-volatile memory application

Abstract: Stable and persistent bipolar resistive switching was observed in an organic diode with the structure of indium-tin oxide (ITO)/bis(8-hydroxyquinoline) cadmium (Cdq2)/Al. Aggregate formation and electric field driven trapping and de-trapping of charge carriers in the aggregate states that lie in the energy gap of the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) of the organic molecule were proposed as the mechanism of the observed bipolar resistive switching, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…[1][2][3][4][5][6] Recently, the organic memory devices have inspired more and more attention for their potential use in substituting inorganic ones to satisfy the demand for inexpensive and high density data storage media. [7][8][9][10][11][12][13][14][15] Many organic materials including small molecular and polymer have achieved the memory effect. [7][8][9][10][11][12][13][14][15] Reddy et al found bias-symmetrical unipolar resistance switching effect in indium tin oxide/ tris-(8-hydroxy-quinoline)aluminum(Alq 3 )/Al nanoparticles/Alq 3 /Al system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] Recently, the organic memory devices have inspired more and more attention for their potential use in substituting inorganic ones to satisfy the demand for inexpensive and high density data storage media. [7][8][9][10][11][12][13][14][15] Many organic materials including small molecular and polymer have achieved the memory effect. [7][8][9][10][11][12][13][14][15] Reddy et al found bias-symmetrical unipolar resistance switching effect in indium tin oxide/ tris-(8-hydroxy-quinoline)aluminum(Alq 3 )/Al nanoparticles/Alq 3 /Al system.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] Many organic materials including small molecular and polymer have achieved the memory effect. [7][8][9][10][11][12][13][14][15] Reddy et al found bias-symmetrical unipolar resistance switching effect in indium tin oxide/ tris-(8-hydroxy-quinoline)aluminum(Alq 3 )/Al nanoparticles/Alq 3 /Al system. [16] They believed that the charge transfer between Alq 3 and Al nanoparticles induced by the electrical field was responsible for the resistance switching.…”
Section: Introductionmentioning
confidence: 99%